2016
DOI: 10.1016/j.jval.2016.09.1323
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Treatment Comparison of Ustekinumab Versus Other Biologics In Moderate To Severe Crohn’s Disease: A 1-Year Treatment Sequence Analysis

Abstract: Objectives: Graft-versus-host disease (GVHD) is a severe complication of allogenic stem cell transplantation. Preliminary data suggest the potential role of ruxolitinib as a new treatment option in patients with corticosteroid-refractory GVHD. The aim of the present study was to explore the effectiveness and safety of ruxolitinib as a salvage therapy in this population. MethOds: A single-center, retrospective, observational study was carried out. Inclusion criteria: all patients with corticosteroidrefractory G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Similar to cohort studies, the observation from indirect comparisons of randomised trials is also conflicting. For instance, Pacou et al suggested a higher likelihood for superior efficacy with ustekinumab compared to vedolizumab in anti‐TNF refractory Crohn's disease in an indirect treatment comparison of patients from randomised trials of various biologics though the results failed to achieve statistical significance 16 . Another indirect comparison study noted no significant differences in safety or efficacy between the two agents in treating anti‐TNF refractory Crohn's disease 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar to cohort studies, the observation from indirect comparisons of randomised trials is also conflicting. For instance, Pacou et al suggested a higher likelihood for superior efficacy with ustekinumab compared to vedolizumab in anti‐TNF refractory Crohn's disease in an indirect treatment comparison of patients from randomised trials of various biologics though the results failed to achieve statistical significance 16 . Another indirect comparison study noted no significant differences in safety or efficacy between the two agents in treating anti‐TNF refractory Crohn's disease 17 .…”
Section: Discussionmentioning
confidence: 99%
“…A treatment sequence analysis was therefore the most plausible option to obtain long-term relative efficacy. Not only did this increase the comparability between maintenance trial placebo arms, it also allowed an evaluation of effect over the full treatment sequence [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…41 publications reporting results from 31 different RCTs met the inclusion criteria. Network meta-analyses (NMAs) of short-term efficacy (probabilities of response or remission) for the induction phase were conducted for each population using a Bayesian framework [ 36 ]. As the identified maintenance trials were deemed not comparable for an NMA, comparative efficacy for the maintenance phase was estimated by means of a treatment sequence analysis, considering both induction and maintenance data.…”
Section: Methodsmentioning
confidence: 99%
“…Ustekinumab is a drug treatment in the latter category, targeting interleukin (IL)-12 and IL-23, that is indicated for the treatment of adult patients with moderately to severely active CD who have had an inadequate response with, lost response to, or were intolerant to either conventional therapy or a TNFα antagonist or have medical contraindications to such therapies [ 1 ]. The positioning of UST in particular versus anti-integrin medications is a topic of active discussion in the clinical literature [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%